The Relationship of Student's Knowledge Level with Anxiety and Precautions the Spread Covid19 in West Nusa Tenggara - Kholik Kholik; Ni Ketut Alit Suarti; Eneng Garnika; Moch Taufik Hidayatullah (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: The level of knowledge of college students about Coronavirus-19 (Covid19) will affect to precaution the spread of this disease. Students as intellectuals can be at the forefront of breaking the chain of the spread of Covid19. The purpose of this study was to determine the relationship between the knowledge of Mandalika University of Science (UNDIKMA) college students about the spread of Covid19 and the level of anxiety and precaution the spread of Covid19. Method: This study used a cross-sectional survey with a questionnaire. The questionnaire was distributed to 38 of 325 UNDIKMA college students registered in PDDikti with the purposive sampling method. The modified questionnaire instrument from the WHO Survey Tool and Guidance was sent via email and Whatsapp from May to June 2020. Data on the level of college student's knowledge about the spread of Covid19, anxiety and precautions the spread of Covid19 will be analyzed using the chi-square test. Result and Discussion: The level of college student's knowledge with a high category about the spread of Covid19 was 52.6%, the level of college student's anxiety with a high category was 57.9%, and the level of precaution the spread of Covid19 for college students with a good category was 55.3% from 38 students. The results of the bivariate analysis on the relationship between the level of college student's knowledge about the spread of Covid19 and the level of anxiety were not significant with p> 0.05 (p-value = 0.064), the relationship between the level of college student's knowledge about the spread of Covid19 and the precaution of the spread of Covid19 not significant with p> 0.05 (p-value = 0.064).Conclusion: The high level of college student's knowledge of Mandalika University of Science (UNDIKMA) about the spread of Covid19 showed no a significant relationship with anxiety and precautions the spread Covid19 in West Nusa Tenggara at pandemic situation so learning models that can reduce anxiety and raise awareness to take precaution the spread of Covid19 are needed in a disease pandemic situation.